Variations of Greetings in the Social Interaction of Lecturers and Students of the Faculty of Cultural Sciences at Khairun University (A Sociolinguistic Review) - Andriani, Andriani; Muhammad, Ikmal (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This research aims to analyze the variations in greetings for social interactions between lecturers and students used by students and lecturers, which is multilingual based in the Faculty of Cultural Science and the factors of using it.This research is hoped to be one of local language documentation and develop character-based local wisdom at school. The method used in this research is qualitative descriptive to collect information concerning the variationsin greetings in their social interaction at the Faculty of Cultural Science at Khairun University. The result of the research showed that there are a variety of terms of address in various languages. Kinds of address terms consist ofkinship and non-kinship terms. Most of the variations in greetings used during interaction are non-kinship, which aims to joke and familiarize themselves.